2018
DOI: 10.1177/1526602818773085
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Proximal Sealing Rings of the Anaconda Stent-Graft After Endovascular Aneurysm Repair

Abstract: Purpose: To provide insight into the evolution of the saddle-shaped proximal sealing rings of the Anaconda stent-graft after endovascular aneurysm repair (EVAR). Methods: Eighteen abdominal aortic aneurysm patients were consecutively enrolled in a single-center, prospective, observational cohort study (LSPEAS; Trialregister.nl identifier NTR4276). The patients were treated electively using an Anaconda stent-graft with a mean 31% oversizing (range 17–47). According to protocol, participants were to be followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…23 Age, the number of patent collateral arteries, maximum aneurysm size, and smoking are main factors consistently associated with type II endoleak. 22,24 In our cohort, the small number of patent collateral branches might have contributed to the low rate of type II endoleak.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…23 Age, the number of patent collateral arteries, maximum aneurysm size, and smoking are main factors consistently associated with type II endoleak. 22,24 In our cohort, the small number of patent collateral branches might have contributed to the low rate of type II endoleak.…”
Section: Discussionmentioning
confidence: 88%
“…Factors influencing sealing and fixation consist of conformational changes of ring stents and aorta over time. Koenrades et al 22 evaluated the evolution of the saddle-shaped proximal sealing rings of the Anaconda stent-graft after EVAR. The initially oval-shaped ring conformed symmetrically and become nearly circular through 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Major wrinkles disturbed the flow pattern and caused recirculation and low wall shear stresses, effects that have been linked to thrombus formation. 26 It is interesting to note that after EVAR, endovascular devices continue to expand within the native artery to near nominal oversize, 14 meaning that the rigid geometry used in this study represents a worst case for fabric infolding. In the future, this CFD analysis capability will be validated against experimental data to strengthen its use as a tool in designing new stent grafts to promote smoother flow.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the patient sample, including preoperative anatomical characteristics by standard computed tomography angiography (CTA) imaging, and the image acquisition protocol were reported in a prior publication about the evolution of the Anaconda proximal sealing rings. 17 Sizes of the stent-graft body ranged from 25.5 to 34 mm. The device was oversized by 17% to 47% (mean 31%) based on inner wall diameters from static preoperative CTA scans.…”
Section: Study Design and Patient Samplementioning
confidence: 99%
“…In the present study, we continue analysis of a previously reported patient cohort 17 to seek full understanding of abdominal aortic neck remodeling after Anaconda stentgraft implantation by investigating the geometric evolution of the entire perirenal neck segment above, at, and below the 2 fixation and sealing rings.…”
Section: Introductionmentioning
confidence: 99%